2008
DOI: 10.1159/000116770
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Nutritional Features in Adult Celiac Patients

Abstract: Celiac disease (CD) is a chronic immune-mediated gluten-dependent enteropathy induced by ingestion of gluten-containing products, characterized by intestinal malabsorption and subtotal or total atrophy of intestinal villi, which improves after gluten-free diet (GFD). Untreated patients affected by the classic form of CD are at high risk of malnutrition, but an impairment of nutritional status is frequently reported also in patients with the subclinical form of the disease. Strict adherence to a GFD greatly imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 89 publications
1
18
0
2
Order By: Relevance
“…Lower body weights, BMI, FM and FFM have been reported [29]. Untreated CD patients have a BMI that is approximately 2.3 points lower than that in controls, but this is usually reversible on a GFD.…”
Section: Discussionmentioning
confidence: 99%
“…Lower body weights, BMI, FM and FFM have been reported [29]. Untreated CD patients have a BMI that is approximately 2.3 points lower than that in controls, but this is usually reversible on a GFD.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis -Numerous studies have shown that adults and children with celiac disease who stick to a gluten-free diet have higher BMIs than those who do not (43)(44)(45)(46). This is due in part to the highly available starch in diets based on tapioca, potato, and corn starches.…”
Section: Celiac Diseasementioning
confidence: 99%
“…1,2 An increasing prevalence of the subclinical and silent forms of CD, characterized by few or even absence of symptoms was reported, 3,4 thus the identification of risk groups could represent a key factor for an early diagnosis of CD with consequent decreased risk of developing malignant and nonmalignant complications. [1][2][3] In addition, patients with CD often show an impairment of nutritional status, either those with the classic or the subclinical form of the disease [4][5][6] and strict adherence to GFD was found to improve but not to completely normalize the body composition in these patients. 5,6 A great prevalence of CD was recently reported among patients with low high-density lipoprotein-cholesterol (HDL-C) concentration, 7 probably as a consequence of decreased lipid absorption, reduction in cholesteroltransporting lipoproteins, and decreased apolipoprotein (Apo)-AI secretion from the altered small bowel mucosa.…”
mentioning
confidence: 99%
“…[1][2][3] In addition, patients with CD often show an impairment of nutritional status, either those with the classic or the subclinical form of the disease [4][5][6] and strict adherence to GFD was found to improve but not to completely normalize the body composition in these patients. 5,6 A great prevalence of CD was recently reported among patients with low high-density lipoprotein-cholesterol (HDL-C) concentration, 7 probably as a consequence of decreased lipid absorption, reduction in cholesteroltransporting lipoproteins, and decreased apolipoprotein (Apo)-AI secretion from the altered small bowel mucosa. [7][8][9][10][11][12] In fact, as Apo-AI represents up to 70% of HDL-C particles, a defect in its secretion may determine a reduction in HDL-C in the bloodstream.…”
mentioning
confidence: 99%